1996
DOI: 10.1007/bf00311802
|View full text |Cite
|
Sign up to set email alerts
|

Two types of major venous anomalies associated with abdominal aneurysmectomy: A report of two cases

Abstract: We report herein the cases of two patients with major venous anomalies associated with abdominal aneurysmectomy, one being an isolated left-sided vena cava and the other, a retroaortic left renal vein, and discuss the clinical significance of such anomalies. In the first patient, an isolated left-sided vena cava was correctly diagnosed preoperatively by contrast-enhanced computed tomography (CE-CT) and digital subtraction angiography (DSA) which revealed that the vena cava crossed the normal portion of the aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Unexpected abnormal venous injuries associated with an AAA repair have been reported. Toda et al 9 and Nonami et al 10 reported cases of left renal vein anomalies that were injured and as a result, provoked massive hemorrhaging during an abdominal aortic aneurysm repair. The former performed direct repair and the latter performed ligation of the injured vein.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpected abnormal venous injuries associated with an AAA repair have been reported. Toda et al 9 and Nonami et al 10 reported cases of left renal vein anomalies that were injured and as a result, provoked massive hemorrhaging during an abdominal aortic aneurysm repair. The former performed direct repair and the latter performed ligation of the injured vein.…”
Section: Discussionmentioning
confidence: 99%
“…Circumaortic vein results if there is persistence of the dorsal collar ( Figure 13). The incidence of this anomaly is 1.5% to 16% (34)(35)(36). Care should be taken to avoid misdiagnosis of this condition as retroperitoneal adenopathy (27).…”
Section: Circumaortic Left Renal Veinmentioning
confidence: 99%
“…Davis and Lundbery reported in 270 autopsies a retroaortic left renal vein in 1.8% and circumaortic renal collar in 1.5% (11) Reis and Esentha reported 2.4% incidence of venous collar (12) Brener in 1974, had mentioned two patients with DLRV associated with abdominal aortic aneurysm in a series of 31 major venous anomalies of the renal vein and the inferior vena cava (13). Brener and Nonami emphasized the importance of retroaortic channel indicating the possibility of severe bleeding in this type of patients (14).…”
Section: Discussionmentioning
confidence: 96%